Management strategies and outcomes of thromboembolism prevention in atrial fibrillation co-existing with immune thrombocytopenia: A review of evidence - Omar H. Metwally; Alaa Rahhal; Raghad A. Elsherif; Ahmed M. Elshoeibi; Mohamed Elhadary; Amgad M. Elshoeibi; Ahmed Badr; Basel Elsayed; Mona Al- Rasheed; Awni Alshurafa; Mohamed A. Yassin (International Journal of Cardiology: Heart & Vasculature, 2024)
This review aimed to assess bleeding risks and explore management options in atrial fibrillation (AF) patients with immune thrombocytopenia (ITP), aiming to formulate an optimal therapeutic approach for improved patient prognosis. Employing MeSH terms, a comprehensive search strategy identified articles on bleeding risks and management guidelines in AF combined with ITP. Original research papers were included, while animal studies, reviews, and non-English articles were excluded. From four databases, 1891 articles were initially retrieved, resulting in 10 relevant full-text articles. Eight studies investigated the effectiveness of anticoagulants in managing concurrent AF and ITP, demonstrating reduced bleeding risk and promising outcomes. Two papers explored surgical interventions, particularly left atrial appendage closure, suggesting its safety for AF management in patients with primary hemostatic disorders, including thrombocytopenia. While the pathophysiological mechanisms of AF and ITP remain unclear, anticoagulation regimens exhibited promising reductions in bleeding risks. Larger studies are warranted to enhance understanding and investigate optimal treatments for AF and ITP.